1981
DOI: 10.1111/j.1439-0329.1981.tb00112.x
|View full text |Cite
|
Sign up to set email alerts
|

Ceratocystis fimbriata of plane trees in Italy: biological aspects and control possibility

Abstract: The biology of the patliogciiic agent ol plane tvcc cmkcr {Ceratocystis fimbriata Lplatani), the vectors of the disease and the results of soinc preventive and curative trcitmonts arc described in detail.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 1 publication
0
16
0
1
Order By: Relevance
“…This sequence contains the conservative substitution Cys 3 Ser, but we can note that two other hydrophobins, such as Eas from Neurospora crassa (consensus sequence ϭ CCQ) (44) and Hfb1 from Thricoderma reesei (consensus sequence ϭ CCA) are exceptions to the consensus rule (45). Furthermore, some recent findings obtained by immunolocalization experiments 2 have indicated that cerato-platanin accumulates abundantly on the fungal cell surface, as hydrophobins do.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…This sequence contains the conservative substitution Cys 3 Ser, but we can note that two other hydrophobins, such as Eas from Neurospora crassa (consensus sequence ϭ CCQ) (44) and Hfb1 from Thricoderma reesei (consensus sequence ϭ CCA) are exceptions to the consensus rule (45). Furthermore, some recent findings obtained by immunolocalization experiments 2 have indicated that cerato-platanin accumulates abundantly on the fungal cell surface, as hydrophobins do.…”
Section: Discussionmentioning
confidence: 80%
“…platani Walter, the Ascomycete responsible for canker stain disease (1). This disease is characterized by foliar wilting and spreading lesions that involve phloem, cambium, and extensive regions of sapwood (2,3). The pathogen spreads from tree to tree by means of root grafts of closely spaced plants and, more frequently, through wounds caused by pruning (4).…”
mentioning
confidence: 99%
“…For example, the introduction of the Platanus strain into Europe (Panconesi, 1981/ and the rubber tree strains into Malaysia (Sharpies, 1936) have lead to large-scale tree mortality. We wanted to test the hypothesis that C. albofundus might have been introduced into South Africa.…”
mentioning
confidence: 99%
“…on the crown, trunks or roots of susceptible hosts are responsible for the majority of new infections of plane trees in both urban and rural environments (Panconesi et al, 2003). During sanitary operations, and in addition to wounding of plane trees, considerable amounts of contaminated sawdust may be produced; in this sawdust, the pathogen can survive for long periods (Crone, 1962;Panconesi, 1981;Mutto Accordi, 1988;Grosclaude et al, 1996). Contaminated sawdust may then be transported by wind, machinery, passing vehicles, water courses or, most often, pruning tools and other equipment, and spread the disease over long distances (Walter 1946;Walter et al, 1952;Panconesi, 1999).…”
Section: Spread By Human Assistancementioning
confidence: 99%